URGENSI PENYEGERAAN PELAKSANAAN WARISAN - Andi Herawati Andi Herawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
In QS. al-Nisa '/ 4: 11 contains a sign that God Almighty instructs the person who controls the inheritance to hasten the settlement and distribution of inheritance fairly and well to other heirs based on the divisions that have been determined by Allah and His apostles and have been developed accordingly detailed in KHI as a result of ijtihad mujtahid scholars in accordance with the space, time, situation and conditions in which they berijtihad. Immediate distribution is carried out of course the heirs can receive the part that is due to him, and if postponed means delaying the right of other heirs to have what he should have in accordance with his part. Delaying the distribution of inheritance as a trigger for future disasters in the family and also causes feelings of tyranny among heirs that have an impact on family relationships can crack